Structural insights into distinct mechanisms of RNA polymerase II and III recruitment to snRNA promoters - Syed Zawar Shah; Thomas N. Perry; Andrea Graziadei; Valentina Cecatiello; Thangavelu Kaliyappan; Agata D. Misiaszek; Christoph W. Müller; Ewan P. Ramsay; Alessandro Vannini (Nature Communications)
Abstract RNA polymerase III (Pol III) transcribes short, essential RNAs, including the U6 small nuclear RNA (snRNA). At U6 snRNA genes, Pol III is recruited by the snRNA Activating Protein Complex (SNAPc) and a Brf2-containing TFIIIB complex, forming a pre-initiation complex (PIC). Uniquely, SNAPc also recruits Pol II at the remaining splicesosomal snRNA genes (U1, 2, 4 and 5). The mechanism of SNAPc cross-polymerase engagement and the role of the SNAPC2 and SNAPC5 subunits remain poorly defined. Here, we present cryo-EM structures of the full-length SNAPc-containing Pol III PIC assembled on the U6 snRNA promoter in the open and melting states at 3.2–4.2 Å resolution. The structural comparison revealed differences with the Saccharomyces cerevisiae Pol III PIC and the basis of selective SNAPc engagement within Pol III and Pol II PICs. Additionally, crosslinking mass spectrometry localizes SNAPC2 and SNAPC5 near the promoter DNA, expanding upon existing descriptions of snRNA Pol III PIC structure.